2016
DOI: 10.1097/cmr.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

Robotic radiosurgery for the treatment of medium and large uveal melanoma

Abstract: The aim of the study was to analyze the local efficacy and eye retention rate after frameless, image-guided robotic radiosurgery against uveal melanoma. A total of 217 patients, mostly with medium and large unilateral uveal melanomas (3% small, 62% medium, and 35% large) were treated. The median age was 64 years (range 21-95 years). All patients underwent a single-session procedure beginning with retrobulbar anesthesia, followed by MRI and computerized tomography scanning to generate the treatment plan. The tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 33 publications
1
26
0
11
Order By: Relevance
“…However, their case series was small, and the follow-up period was short. In a later paper from the same group, Eibl-Lindner et al 19 reported the results of 18-22 Gy SRS on 217 patients with medium or large uveal melanoma and reported a globe preservation rate of 86.7% at 3 years and 73% at 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, their case series was small, and the follow-up period was short. In a later paper from the same group, Eibl-Lindner et al 19 reported the results of 18-22 Gy SRS on 217 patients with medium or large uveal melanoma and reported a globe preservation rate of 86.7% at 3 years and 73% at 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…They realized a comparable safety profi le in terms of incidence of SG to both radiation modalities. Irradiation techniques have a great importance for eye retention, but SG with tumor recurrence make up 82-90 % of reasons for secondary enucleation (37, 41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Treatments have been typically delivered using a single fraction on a Gamma Knife unit with retrobulbar anesthesia [ 9 ]. Reports using the CyberKnife platform are less common with the largest experience being from Munich where patients are treated with a regimen analogous to that used on the Gamma Knife (single fraction using retrobulbar anesthesia) [ 10 ]. In the German series of more than 200 patients, the estimated five-year local failure rate was approximately 30%, and 30% of patients retained serviceable eyesight (defined as 6/20 or better).…”
Section: Discussionmentioning
confidence: 99%